Implementasi TOPSIS Pada Sistem Rekomendasi Pemilihan Lapangan Tenis Di Malang Berbasis Lokasi - Heru Budiyanto; Ratih Kartika Dewi; Sutrisno Sutrisno (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Many people, especially in Malang city, like to play sports in tennis courts, so more tennis courts are spread out in Malang. However, with so many places in the tennis court, sometimes many people do not know which one is better for training. Seeing this problem, the researchers built a recommendation system for tennis courts in Malang. This system was developed using the Android-based native mobile development model so that it can be reached by many people. With this application, the community can get recommendations on suitable tennis courts based on their location using GPS. The recommendation system for the tennis court was designed using the TOPSIS method with 3 criteria data, namely the distance from the user's location using haversine calculations, tennis court prices per hour, and rating. The results of functional testing, the system built has fulfilled the functional requirements with a 100% valid value, Testing the algorithm validation between manual calculations and system calculations shows a 100% match in the form of alternative sequences and the value of each alternative, and Rank Consistency Testing by reducing and the addition of criteria is 2 criteria and 4 criteria compared to the initial criteria to get a consistent ranking result.